Knowledge and Attitude Towards Medical Ethics of Artificial Intelligence Among Healthcare Workers in Egypt: Knowledge And Attitude Towards Medical Ethics Of Artificial Intelligence Among Healthcare Workers In Egypt. - Rohym, Heba; Saleh, Amal (International Journal of Medical Toxicology and Forensic Medicine, 2025)
Background: Hospital care data can be leveraged to benefit patients through various technological advancements in the artificial intelligence (AI) era. This will ultimately lead to improved outcomes and more efficient services. The purpose of our study was to assess physicians’ opinions and knowledge regarding the ethical application of AI in Medicine in Fayoum, Egypt. Methods: We conducted a cross-sectional survey among doctors and nurses working at Fayoum Hospitals. A standardized, validated questionnaire assessing knowledge, attitudes, and medical ethics related to AI was administered in both Arabic and English. The study was conducted from July 2024 to December 2024, spanning six months. Results: Approximately one-fourth of participants thought that AI would help provide medical assistance in underserved areas, whereas 24% believed that it would be more useful in biopharmaceutical, 18% felt that it would be more useful in making diagnosis, 14% believed that it would be helpful in social awareness program, 11% believed that it would be useful in direct treatment and 7% believed that it would help make treatment decision. There was a statistically significant difference between the study groups in their knowledge and attitudes regarding the medical ethics of Artificial Intelligence. Physicians had higher knowledge scores than nurses (p=0.032). There was a statistically significant difference between the study groups. Physicians had a higher attitude score than nurses (p=0.026). Healthcare workers in medical departments had higher Knowledge scores than those in surgical departments (p=0.031) and higher attitude scores than those in surgical departments (p=0.025). Conclusion: Healthcare workers showed positive attitudes but moderate knowledge about the ethical use of AI. Physicians and those in medical departments scored higher, highlighting the need for targeted education to support the responsible integration of AI in healthcare.